Implementasi Program Bantuan UMKM dalam Menjalankan Pemberdayaan Masyarakat di Kecamatan Ilir Timur 1 Kota Palembang - Yudistira, Bram (Jurnal Publisitas, 2023)
This research was conducted aiming to find out whether the implementation of the Presidential Assistance program carried out by the District in increasing MSMEs in Ilir Timur 1 District, Palembang City. The problems that occur in the field are lack of business capital, and business permits through applying for collateral credit, the problem when making submissions is hampered at BI checking even though, legality is the key to developing a business and a requirement for obtaining capital assistance. This research uses qualitative methods, qualitative research involves important efforts, including asking questions, procedures, collecting specific data from participants, analyzing data. Empowering people, using the theory of Edward III which has 4 variables that influence a policy, namely, [1] Communication, [2] Resources, [3] Disposition, and [4] Bureaucratic Structure. The results in this study are that the empowerment of MSME owners can be directed so that they can increase productivity and competitiveness and are directed at efforts to foster new entrepreneurs in sectors that have high productivity based on knowledge, technology and local resources, the role of institutions as well as development tools aimed at provide benefits for low-income people, so that data collection is immediately carried out on all the number of MSMEs in Ilir Timur 1 District, Palembang City, and additional personnel for this program.